Promoting vascularization for tissue engineering constructs: current strategies focusing on HIF-regulating scaffolds - Esser, Tilman; Roshanbinfar, Kaveh; Engel, Felix (Expert Opinion on Biological Therapy, 2018)
INTRODUCTION: Vascularization remains one of the greatest yet unmet challenges in tissue engineering. When engineered tissues are scaled up to therapeutically relevant dimensions, their demand of oxygen and nutrients can no longer be met by diffusion. Thus, there is a need for perfusable vascular structures. Hypoxia-inducible factors (HIF) act as transcriptional oxygen sensors and regulate a multitude of genes involved in adaptive processes to hypoxia, including angiogenesis. Thus, targeting HIFs is a promising strategy to induce vascularization of engineered tissues. Areas covered: Here we review current vascularization strategies and summarize the present knowledge regarding activation of HIF signaling by ions, iron chelating agents, α-Ketoglutarate (αKG) analogues, and the lipid-lowering drug simvastatin to induce angiogenesis. Specifically, we focus on the incorporation of HIF-activating agents into biomaterials and scaffolds for controlled release. Expert opinion: Vascularization of tissue constructs through activation of upstream regulators of angiogenesis offers advantages but also suffers from drawbacks. HIFs can induce a complete angiogenic program; however, this program appears to be too slow to vascularize larger constructs before cell death occurs. It is therefore crucial that HIF-activation is combined with cell protective strategies and prevascularization techniques to obtain fully vascularized, vital tissues of therapeutically relevant dimensions.
EVALuna2:102206